The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1039/c2cc16673a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the macrocycle size by the stoichiometry of the applied template ion

Abstract: Reaction of 4-tert-butyl-2,6-diformylphenol with (1R,2R)- or (1S,2S)-1,2-diaminocyclohexane in the presence of 1 equivalent of Zn(2+) ions leads to selective formation of a chiral 2+2 macrocycle. Application of 0.5 equivalent of Zn(2+) ions under the same conditions leads to selective formation of a chiral 3+3 macrocycle, which forms a cavitand-shaped trinuclear double-decker complex with Zn(II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 25 publications
(3 reference statements)
2
38
0
Order By: Relevance
“…As imilar conformation of imine bonds was observedi nt he free macrocycles H 3 1 [20,21] and H 3 3. [22] The overall shapeo ft he trinuclearc omplex [Zn 3 4 2 ] is similart ot hat of the previously reported crystal forms of [Zn 3 1 2 ]g rown from methanolo rc hloroform, [8] as well as the new crystal forms of [Zn 3 1 2 ]g rown from toluene or the ethanol/dichloromethane mixture reported herein ( Figure 3). This shape corresponds to ab arrel, the walls of which are constructed of the macrocyclic ligands and Zn II ions.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As imilar conformation of imine bonds was observedi nt he free macrocycles H 3 1 [20,21] and H 3 3. [22] The overall shapeo ft he trinuclearc omplex [Zn 3 4 2 ] is similart ot hat of the previously reported crystal forms of [Zn 3 1 2 ]g rown from methanolo rc hloroform, [8] as well as the new crystal forms of [Zn 3 1 2 ]g rown from toluene or the ethanol/dichloromethane mixture reported herein ( Figure 3). This shape corresponds to ab arrel, the walls of which are constructed of the macrocyclic ligands and Zn II ions.…”
Section: Resultssupporting
confidence: 84%
“…[4,5] Enantiopure[ 3 + +3] macrocycles derived from trans-1,2-diaminocyclohexane anda romaticd ialdehydes are versatile chiral ligands for the coordination of variousm etal ions. [8][9][10] As imilar [3+ +3] macrocycle derived from 1,2-diaminobenzene has been used to obtain metal-macrocyclef rameworks with enantiomeric pairs of guest binding pockets. [11] We have recently shown that the triphenolic [3+ +3] Schiff-base macrocycle derived from trans-1,2-diaminocyclohexane,H 3 1,o ri ts enantiomer,H 3 2,f orm trinuclear Zn II complexes.I nt hesec ompounds, two deprotonated macrocyclic units are connected by metal ions to form the cage-like molecule [Zn 3 1 2 ]w ith the interior occupiedb ys olvent molecules( Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36] It should be emphasized that the 1,2-cycloalkyldiamines (especially trans-1,2-diaminocyclohexane) were studied in detail in the formation of ([2+2]) imine macrocycles scrutinizing the role of chirality of conformational preorganization. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] It should be emphasized that the 1,2-cycloalkyldiamines (especially trans-1,2-diaminocyclohexane) were studied in detail in the formation of ([2+2]) imine macrocycles scrutinizing the role of chirality of conformational preorganization.…”
Section: Introductionmentioning
confidence: 99%
“…Large macrocyclic Schiff bases and amines obtained in many ways from dicarbonyl compounds and chiral diamines have been studied with special attention paid to their chiral properties, metal binding ability, interactions with DNA, organic guest hosting, catalysis, and formation of porous materials. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] It should be emphasized that the 1,2-cycloalkyldiamines (especially trans-1,2-diaminocyclohexane) were studied in detail in the formation of ([2+2]) imine macrocycles scrutinizing the role of chirality of conformational preorganization. [37][38][39] The mechanism of the imine formation has been recently extensively studied theoretically, [40][41][42][43][44][45][46] but it has not been fully understood yet.…”
Section: Introductionmentioning
confidence: 99%